Finite-Element Model Predicts Current Density Distribution for Clinical Applications of tDCS and tACS - Neuling, Toralf; Wagner, Sven; Wolters, Carsten H.; Zaehle, Tino; Herrmann, Christoph S. (Frontiers in Psychiatry, 2012)
Transcranial direct current stimulation (tDCS) has been applied in numerous scientiﬁc studies over the past decade. However, the possibility to apply tDCS in therapy of neuropsychiatric disorders is still debated. While transcranial magnetic stimulation (TMS) has been approved for treatment of major depression in the United States by the Food and Drug Administration (FDA), tDCS is not as widely accepted. One of the criticisms against tDCS is the lack of spatial speciﬁcity. Focality is limited by the electrode size (35 cm2 are commonly used) and the bipolar arrangement. However, a current ﬂow through the head directly from anode to cathode is an outdated view. Finite element (FE) models have recently been used to predict the exact current ﬂow during tDCS. These simulations have demonstrated that the current ﬂow depends on tissue shape and conductivity. To face the challenge to predict the location, magnitude and direction of the current ﬂow induced by tDCS and transcranial alternating current stimulation (tACS), we used a reﬁned realistic FE modeling approach. With respect to the literature on clinical tDCS and tACS, we analyzed two common setups for the location of the stimulation electrodes which target the frontal lobe and the occipital lobe, respectively. We compared lateral and medial electrode conﬁguration with regard to their usability. We were able to demonstrate that the lateral conﬁgurations yielded more focused stimulation areas as well as higher current intensities in the target areas. The high resolution of our simulation allows one to combine the modeled current ﬂow with the knowledge of neuronal orientation to predict the consequences of tDCS and tACS. Our results not only oﬀer a basis for a deeper understanding of the stimulation sites currently in use for clinical applications but also oﬀer a better interpretation of observed eﬀects.